a Schema Extraction of Document-Oriented Database for Data Warehouse - A. Nurul Istiqamah; Kemas Rahmat Saleh Wiharja (School of Computing, Telkom University, 2021)
The data warehouse is a very famous solution for analyzing business data from heterogeneous sources. Unfortunately, a data warehouse only can analyze structured data. Whereas, nowadays, thanks to the popularity of social media and the ease of creating data on the web, we are experiencing a flood of unstructured data. Therefore, we need an approach that can